A Service Quality Review of Medical Record Department In Private Hospital, South Jakarta - Eka Widya Rita P.; Ratna Indrawati; Lily Widjaja (Journal of Multidisciplinary Academic, 2021)
The medical record is a document containing the patient's identity, history, physical examination, diagnosis, supporting tests and patient treatment. Here, the excellent medical record system service is one of the standard hospital services that function to help the patient care process. Thus, in this study to obtain empirical evidence and field data regarding the input, process, output, and impact in the medical records department at the outpatient installation of a Class-B Private Hospital at South Jakarta. Here, we used the data observation in June-July 2020 using the Mix Method with retrieval technique of Purposive Sampling sample of 72 medical records and 10 medical record staff respondents. The study results shows that the completeness of medical records reached 93.1% with the accuracy of the data around 87.5% and the distribution reached 58.3% with an average distribution time of 11 minutes / medical record. Also, in the effective category, the reliability value was 92%, responsiveness in was 100%, assurance was 100%, and empathy was 100% while tangibles in the less effective category were 67%. Thus, it means that the medical records service system in the outpatient installation at X Private Hospital Class B, South Jakarta, was in an effective category. Further research should be conducted to obtain more in-depth information.